Honoris causa : ereleden van de Koninklijke Academie van Beeldende Kunsten Den Haag. - Rehorst, Chris; van Gils, Marianne; van Toorenburg, Carmen C. (Den Haag : Koninklijke Academie van Beeldende Kunsten, 1992)
Antonowa, Irina ; Bayer, Herbert ; Beljon, Shirley ; Bolomey, Roger H. ; Buckminster Fuller, Richard ; Burle Marx, Roberto ; Calder, Alexander ; Chagall, Marc ; Darie, Sandu ; Eloul, Kosso ; Fonseca, Gonzalo ; Friedman, Yona ; Gispen, Willem H. ; Goeritz, Mathias ; Grès, Alix ; Hicks, Sheila ; Hollein, Hans ; de Kooning, Willem ; Kounellis, Jannis ; Kramer, Friso ; Lüpertz, Markus ; Nivola, Constantino ; Quant, Mary ; Redstone, Louis G. ; Rogers, Richard ; Sandberg, Willem ; Schorske, Carl ; Sebastian ; Sert, José Luis ; Steinberg, Saul ; Takahashi, Kiyoshi ; Visser, Carel ; Zwart, Piet
Nederlands
boek
Keywords: Den Haag